(untitled) (Analysis in Theory and Applications, 2019)
In this paper, a weak type (1,1) estimate is established for the higher order commutator introduced by Christ and Journé which is defined by T[a_1,…,a_l]f(x)=p.v. _R^d K(x-y)(_i=1^lm_x,ya_i)· f(y)dy, where K is the standard Calderόn-Zygmund convolution kernel on R^d (d≥2) and m_x,ya_i=_0^1a_i(sx+(1-s)y)ds.